Adult liver transplantation: A UK clinical guideline - part 1: pre-operation. Issue 5 (25th February 2020) - Millson, Charles; Considine, Aisling; Cramp, Matthew E; Holt, Andrew; Hubscher, Stefan; Hutchinson, John; Jones, Kate; Leithead, Joanna; Masson, Steven; Menon, Krish; Mirza, Darius; Neuberger, James; et al.
Abstract : Liver transplantation is a highly successful treatment for all types of liver failure, some non-liver failure indications and liver cancer. Most referrals come from secondary care. This first part of a two-part guideline outlines who to refer, and how that referral should be made, including patient details and additional issues such as those relevant to alcohol and drug misuse. The process of liver transplant assessment involves the confirmation of the diagnosis and non-reversibility, an evaluation of comorbidities and exclusion of contraindications. Finally, those making it onto the waiting list require monitoring and optimising. Underpinning this process is a need for good communication between patient, their carers, secondary care and the liver transplant service, synchronised by the transplant coordinator. Managing expectation and balancing the uncertainty of organ availability against the inevitable progression of underlying liver disease requires sensitivity and honesty from all healthcare providers and the assessment of palliative care needs is an integral part of this process.